Machine Learning for Handoffs Classification Based on Effective Communication History - Simbolon, Anita Ira Agustina; Pujiastuti, Maria; Jaya, Indra Kelana; Tarigan, Kerista; Sinambela, Marzuki (Politeknik Ganesha Medan, 2019)
An important step in data effective communication in handoffs process analysis is data exploration and representation. Communication in handoff treatment is crucial to protect the patients and it can lead to patient’s safety, discontinue care of a patient or the cause loss of important information related to the continuum of care. In this case, we use the machine learning technique by using Support Vector Machine for classification the handoffs for twenty weeks to analysis and represented based on the effective communication history. We used handoffs dataset which employed from Arifin Achmad Hospital in Pekanbaru, Indonesia. The result indicated the performance of the designed system was successful and could be used in handoffs analysis based on the effective communication histories in Arifin Achmad Hospital in Pekanbaru, Indonesia.